The last time I saw Paris - Brooks, Richard, 1912-1992; Jaenzon, Julius, 1885-1961; Epstein, Philip G.; Cummings, Jack, 1900-1989; Taylor, Elizabeth, 1932-2011; Metro-Goldwyn-Mayer (United States : Metro Goldwyn Mayer, 1961)
Shortly after the end of World War II, Charles (Van Johnson) returns to Paris where he reminisces about the years he spent living there after the city's liberation. While working at the newspaper "Stars and Stripes" aspiring to become a great writer, he met Helen (Elizabeth Taylor), a beautiful young woman with whom he fell in love and made his wife. Little by little, his economic situation improves and he decides to try to write his great novel by frequenting the bohemian environments of Paris. This will come between him, his wife and his daughter.--
Based on a story by F. Scott Fitzgerlad.
Elizabeth Taylor, Van Johnson, Donna Reed, Eva Gabor, Kurt Kasznar, George Dolenz, Roger Moore.
Editor, John Dunning ; music, Jerome Kern.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 17, 2022)
Keywords: Motion pictures; Film posters; Streaming video